CFD (Computational Fluid Dynamics) Simulation of Hydrodynamic Vortex Turbine Performance: Influence of Notch Angle Variation on Flow Patterns and Efficiency - Sukadana, I Gusti Ketut; Made Suarda; I Putu Widiarta; Ishak Danus (Natural Sciences Engineering and Technology Journal, 2024)
Hydrodynamic vortex turbines (HVTs) offer a promising solution for harnessing renewable energy from low-head water sources. The inlet notch angle, a critical geometric parameter, significantly influences the flow patterns within the turbine basin and, consequently, its overall performance. This study investigates the impact of notch angle variation on HVT efficiency and flow characteristics using computational fluid dynamics (CFD) simulations. A 3D model of an HVT was developed and simulated using ANSYS Fluent. The notch angle was varied between 7° and 15° in 2° increments. The k-ω SST turbulence model was employed to capture the complex flow behavior. Velocity and pressure contours were analyzed to understand the flow patterns, while turbine performance metrics, including torque, power output, and efficiency, were computed. The results revealed a strong correlation between notch angle and turbine performance. Increasing the notch angle led to higher flow velocities in the turbine basin, resulting in enhanced vortex formation and increased energy extraction. Consequently, both power output and efficiency improved with larger notch angles. The optimal notch angle, balancing efficiency and practical considerations, was identified. This study demonstrates the critical role of notch angle in HVT design. CFD simulations provide valuable insights into the flow dynamics and performance optimization of these turbines. The findings contribute to the advancement of HVT technology for sustainable micro-hydro power generation.